Konservasi Mangrove sebagai Implementasi Program Desa Tangguh Bencana (DESTANA) dalam mengatasi Banjir Rob di Kabupaten Cirebon - Bella Oktavianita; Febby Amanda Putri; Adriani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Increased human activities in the coastal area will cause several problems, one of which is the tidal flooding that occurs due to excessive pumping of groundwater so that the sea level is higher than the groundwater level. The loss of mangroves causes the coast to lose its protective system against incoming waves so that the beach is increasingly vulnerable to tidal flooding. Therefore, this program aims to conserve mangroves as an effort to implement the DESTANA program in dealing with tidal floods in Cirebon district. The method used in this activity is socialization and conservation. The results show that the implementation in the DESTANA program, namely mangrove conservation can be carried out. Mangroves planted in this conservation activity are 5000 propagules in Grogol Village and 1500 Propagul in Gebangmekar Village. This program was carried out well because it collaborated with the local Karangtaruna. Keywords: Conservation, mangroves, coastal areas.